An Equilibrium Theory of Nominal Exchange Rates - Marcus Hagedorn (Center for Economic Studies and ifo Institute (CESifo), 2021)
This paper proposes an equilibrium theory of nominal exchange rates, which offers a new perspective on various issues in open economy macroeconomics. The nominal exchange rate and portfolio choices are jointly determined in equilibrium, thus providing a new approach to overcoming the indeterminacy results in Kareken and Wallace (1981). The distinctive features of this theory are that the nominal exchange rate is determined in international financial markets, that the risk premium and UIP deviations are fully endogenous equilibrium objects and that the real exchange rate inherits its properties from the nominal exchange rate. In terms of policy, this novel theory implies that a country with an exchange rate peg and free asset mobility faces a tetralemma and not a trilemma, because it loses not only monetary policy independence but also fiscal policy independence.
Keywords: D52; E31; E43; E52; E62; E63; 330; exchange rate; determinacy; incomplete markets; monetary and fiscal policy; international asset flows